2023
DOI: 10.1186/s12964-023-01138-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting HIF-1 signaling alleviates HTRA1-induced RPE senescence in retinal degeneration

Abstract: Background Age-related macular degeneration (AMD), characterized by the degeneration of retinal pigment epithelium (RPE) and photoreceptors, is the leading cause of irreversible vision impairment among the elderly. RPE senescence is an important contributor to AMD and has become a potential target for AMD therapy. HTRA1 is one of the most significant susceptibility genes in AMD, however, the correlation between HTRA1 and RPE senescence hasn’t been investigated in the pathogenesis of AMD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Conversely, we found that Igfbp3 expression decreased when Hif1a was knocked down, regardless of the sugar type used. The induction of Hif1a influence the production of cytokines associated with the senescence-related phenotype 33,56 , aligning with our findings that demonstrate an increase in P16 and P21 immunosignals. Interestingly, we showed that IL4, IL8, and IL10 were increased in the fructose containing medium along with the reduction in GDF15, a growth factor that supports proliferation 26 .…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, we found that Igfbp3 expression decreased when Hif1a was knocked down, regardless of the sugar type used. The induction of Hif1a influence the production of cytokines associated with the senescence-related phenotype 33,56 , aligning with our findings that demonstrate an increase in P16 and P21 immunosignals. Interestingly, we showed that IL4, IL8, and IL10 were increased in the fructose containing medium along with the reduction in GDF15, a growth factor that supports proliferation 26 .…”
Section: Discussionsupporting
confidence: 91%
“…HTRA1 plays an important role in vascular homeostasis by regulating signaling pathways or refolding, translocation, and degradation of extracellular matrix proteins, thereby directly or indirectly regulating angiogenesis and vascular remodeling, and vascular and related structural dysfunction caused by abnormal function of the HTRA1 gene is an important initiator and high risk factor. This article suggests that more research on vascular diseases involving cardiovascular, 120 renal, 121 and hepatic diseases 122 should include HTRA1 as an important research target, and even in the process of tissue repair and regeneration, 123 scarring, 124 senescence, 125 , 126 and pregnancy complications 87 should include HTRA1 as an indispensable research component.…”
Section: Problems and Prospectsmentioning
confidence: 99%
“… 19 The role of HTRA1 in AMD cellular senescence is multifaceted, involving oxidative stress response, mitochondrial function, and regulation of hypoxia-inducible factor-1 and p38 mitogen-activated protein kinase signaling pathways, inducing RPE senescence, extracellular matrix deposition, and AMD-related choroidal vasculopathy. 20 , 21 The differential expression of bone morphogenetic protein 4 (BMP4) across AMD subtypes is intimately linked to cellular senescence. In dry AMD patients, high BMP4 expression activates p53 via the Smad and p38 signaling pathways, increases p21 WAF1/CIP1 expression, and decreases pRb levels, thereby mediating RPE senescence.…”
Section: Amd and Cellular Senescencementioning
confidence: 99%